Weediness of spring cereal ear crops depends on the forecrop, tillage, fertilizers and herbicides - Hutianskyi, R.; Popov, S.; Popova, K.; Kuzmenko , N. (Quarantine and plant protection, 2024)
Goal. To analyze the species composition of weeds, their dominant role and to determine the type and level of weediness of spring cereal ear crops depending on different forecrops, methods of basic tillage, fertilization systems and herbicides in the conditions of the Eastern Forest-Steppe of Ukraine. Methods. The investigations were conducted in field experiments of spring cereal crops (barley, wheat, triticale) in a stationary field, fixed nine-course-fallow-grain-row crop rotation by means of route surveys. results. According to the data of 2016—2018, during the cultivation of spring cereal ear crops in crop rotation after soybeans, corn for grain and sugar beets as forecrops, 38, 34 and 45 species of weeds were identified, respectively. In total, 52 species of weed plants were found in the crops, of which 27 species occurred after all forecrops. The largest number of weeds in agrocenoses was represented by early and late spring species (48.9—58.8%), and the second and third places were respectively occupied by wintering, winter and biennial (26.5—31.1%), and perennial (14.7—20.0%). The main species of weeds in cereal crops were: after soybean forecrop, Setaria glauсa, Echinochloa crus-galli, Chenopodium album, Ambrosia artemisiifolia, Cirsium arvense, Convolvulus arvensis; after corn for grain forecrop, S. glauсa, E. crus-galli, C. album, Amaranthus retroflexus, Solanum nigrum, A. artemisiifolia, Polygonum lapathifolium, C. arvense, C. arvensis; after sugar beets forecrop, S. glauсa, E. crus-galli, C. album, A. retroflexus, S. nigrum, A. artemisiifolia, P. lapathifolium, C. arvense, Sonchus arvensis, C. arvensis. The largest number of weeds (33 species each) was found after sugar beets forecrop in the control (plowing, without fertilizers) and after chisel tillage (manure, after effect 30 t/ha + N30P30K30). Herbicides and forecrops significantly influenced the dominant and subdominant positions of certain weed species. In the crops, the cereal annual-bicotyledonous-root-sprouting type of weediness predominated (44.2%). The type of weediness of the crops depended on the use of agricultural practices in the years of research. Conclusions. In the conditions of the Eastern Forest-Steppe of Ukraine, weediness of spring cereal ear crops depended significantly on the forecrop, the method of basic tillage, the fertilization system, and the use of herbicides.